Charging and Discharging Characteristics of a Battery-Capacitive Energy Storage Device for Stand-Alone Photovoltaic System - V. P. Vasilevich; М. Y. Zbysinskaya (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The purpose of the research is to study the charging-discharging characteristics of a hybrid energy storage device which consists of two parallel connected battery and capacitive parts to assess the work efficiency of its circuit design as a part of standalone photovoltaic system. The charge current kinetics of a hybrid storage device from a solar panel was carried out under natural conditions at a specific power of incident solar radiation of 800–850 W/m2. The discharge current kinetics of battery and capacitive storages were obtained with a resistive load and disconnected solar battery. The dynamics of charging and discharging processes of the battery and capacitive parts of the energy storage device were monitored by the voltage rise/fall rate. The battery part of the drive is charging and starting the device based on a lead-acid gel battery with a charging capacity of 11 A·h, 12.8 V maximum voltage, and 15 A maximum discharge current. The capacitive part consisted of a new generation INSPECTOR Booster supercapacitor starting the device with an electrostatic capacity of 80 F, 15.5 V voltage, and 800 A starting current. As the energy source a solar battery was used, with a 12 V nominal voltage and 100 W peak power. A 6 Om rheostat with 15 A consumption current was used as a load during the storage device discharge. A Morningstar ProStar-15 charging/discharging controller with a pulse-width modulation function was used to monitor and control the photovoltaic system. Quantitative charging and discharging characteristics of a battery-capacity energy storage device were obtained for the use in the development of standalone photovoltaic system.